1999
DOI: 10.3171/jns.1999.90.6.1105
|View full text |Cite
|
Sign up to set email alerts
|

Antisense preproendothelin-oligoDNA therapy for vasospasm in a canine model of subarachnoid hemorrhage

Abstract: Antisense preproET-1 oligodeoxynucleotide treatment, when combined with clot lysis caused by rtPA, reduced vasospasm in the canine model of SAH, and this effect appeared to be related to reduced ET-1 synthesis. The results of this experiment support a causative role for ET-1 early in the course of vasospasm development in dogs. The apparent additive therapeutic effects of antisense and fibrinolytic treatments could be due to clot lysis, which allows better delivery of oligodeoxynucleotides to arteries within t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2000
2000
2008
2008

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(15 citation statements)
references
References 44 publications
1
14
0
Order By: Relevance
“…Even though Ohkuma et al 11 showed a mild reduction in vasospasm in a canine model using an antisense therapy, we observed a marked attenuation of vasospasm in the present study. Different observations between these 2 studies might be caused by differential targeting of mRNAs by antisense ODN.…”
Section: Antisense Therapy For Vasospasmsupporting
confidence: 29%
“…Even though Ohkuma et al 11 showed a mild reduction in vasospasm in a canine model using an antisense therapy, we observed a marked attenuation of vasospasm in the present study. Different observations between these 2 studies might be caused by differential targeting of mRNAs by antisense ODN.…”
Section: Antisense Therapy For Vasospasmsupporting
confidence: 29%
“…10 -12 Third, antagonists of ET-1 attenuate vasospasm in experimental models of SAH. 2,[13][14][15] However, mechanisms of release, cellular origin, or even the compartment of release of ET-1 in SAH are still unknown. So far, production of ET-1 has been attributed to endothelial cells, 16 smooth muscle cells, 17 neurons, 18 or astrocytes.…”
mentioning
confidence: 99%
“…We counted cells in each layer of the arterial wall at various times after SAH to determine if changes were due to an increase in number of cells and to establish whether genomic deoxyribonucleic acid (gDNA) could be used as a housekeeping standard. The results call into question literature reporting changes in gene expression after SAH (Hino et al, 1996b;Sayama et al, 1998;Ohkuma et al, 1999;Onda et al, 1999;Suzuki et al, 1999;Ono et al, 2000;Miyagi et al, 2000;Aihara et al, 2001) and suggest that there is significant cell proliferation within certain layers of the arterial wall after SAH in dogs.…”
Section: Introductionmentioning
confidence: 72%
“…The levels of mRNA for these genes has been assumed to be stable in some prior studies (Hino et al, 1996a;Sayama et al, 1998;Ohkuma et al, 1999;Onda et al, 1999;Suzuki et al, 1999;Ono et al, 2000;Miyagi et al, 2000;Aihara et al, 2001). If housekeeping gene mRNA increases, then genes reported to have increased expression might actually have been increased even more.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation